Biogenic Zinc Oxide Nanoparticles Improve In Vitro Growth of Blueberries - Luca Regni; Daniele Del Buono; Maurizio Micheli; Simona Lucia Facchin; Arianna Cesarini; Dario Priolo; Primo Proietti (Horticulturae)
Nanotechnology offers promising applications in agriculture by enhancing crop growth, yield, and antioxidant defenses. This study is the first to evaluate the effect of biogenic zinc oxide nanoparticles (ZnO-NPs) on the in vitro growth of two blueberry cultivars, Brigitta and Duke. The ZnO-NPs were synthesized biogenically using an extract of Lemna minor L., which is a free-floating aquatic plant, as a capping and modulating agent, and were added to the plant’s growth media at different dosages (0, 2, 6, and 18 mg L−1). The ZnO-NPs significantly increased the shoot number, fresh biomass, and dry weight in both cultivars without affecting shoot vitality, length, or basal callus formation. Moreover, the increases in carotenoids in both cultivars, as well as chlorophyll and and soluble proteins in the ‘Brigitta’ cultivar, confirm the prompted benefits and possibly evidence genotype-specific metabolic adaptations in response to ZnO-NPs. These results demonstrate that biogenic ZnO-NPs can effectively promote the in vitro growth of blueberry explants, offering improvements in micropropagation efficiency.